Briefing: Blast effects on biological systems - Masouros,SD; Brown,KA; Clasper,J; Proud,WG (Proceedings of the Institution of Civil Engineers Engineering and Computational Mechanics, 2013)
A signature of current conflicts is the use of buried improvised explosive devices to cause injury to military personnel and damage to their vehicles. Explosive devices also cause injuries to non-military populations in current and former conflict zones. The nature and placement of the explosive charge has a marked effect on the loading experienced. In all situations, damage to tissues occurs when the energy and loading rate exceeds that which the human body can support. Currently, it is difficult to predict the various time-dependent effects of blast injury because of the complexities of the rapid initial accelerations, the loading geometries and the heterogeneous nature of the tissues that can be damaged. An outline of the ways in which one may study how explosive energy interacts with biological systems is presented along with a discussion of how the data generated can be used to develop improved, costeffective strategies for studying blast injury processes.